2016
DOI: 10.1021/acsami.5b12658
|View full text |Cite
|
Sign up to set email alerts
|

Hybridizing Poly(ε-caprolactone) and Plasmonic Titanium Nitride Nanoparticles for Broadband Photoresponsive Shape Memory Films

Abstract: Plasmonic nanoparticles can confine light in nanoscale and locally heat the surrounding. Here we use titanium nitride (TiN) nanoparticles as broadband plasmonic light absorbers and synthesized a highly photoresponsive hybrid cross-linked polymer from shape memory polymer poly(ε-caprolactone) (PCL). The TiN-PCL hybrid is responsive to sunlight and the threshold irradiance was among the lowest when compared with other photoresponsive shape memory polymers studied previously. Sunlight heating with TiN NPs can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…Using this method, they were able to obtain full shape recovery of their polymers upon irradiation with solar light at lower thresholds than previously reported with intensities between 130 and 160 mW cm –2 while no recovery was observed for the same polymer without the nanoparticles added. [ 166 ] Leng et al made use of carbon nanoparticles in combination with a shape‐memory polymer to show the possibility of a precisely localized trigger allowing for precise control over the location of the shape recovery. [ 167 ]…”
Section: Photoresponsive Shape‐memory Polymersmentioning
confidence: 99%
“…Using this method, they were able to obtain full shape recovery of their polymers upon irradiation with solar light at lower thresholds than previously reported with intensities between 130 and 160 mW cm –2 while no recovery was observed for the same polymer without the nanoparticles added. [ 166 ] Leng et al made use of carbon nanoparticles in combination with a shape‐memory polymer to show the possibility of a precisely localized trigger allowing for precise control over the location of the shape recovery. [ 167 ]…”
Section: Photoresponsive Shape‐memory Polymersmentioning
confidence: 99%
“…Making use of these superior properties, Li et al developed a TiN-SiO 2 -TiN broad band solar absorber, which can absorb 95% of light over the range of 400-800 nm with 240 nm thick device [35]. Similarly, Ishii et al fabricated TiN-ZnO-TiN structure, which showed superior performance in comparison to gold in visible region [36]. Both these devices were chemically robust, stable at high temperature and can be used in several emerging technologies such as solar-thermophotovoltaics (STPV), heat-assisted magnetic recording (HAMR).…”
Section: Refractory Electronics and Plasmonicsmentioning
confidence: 99%
“…Shape memory polymers (SMPs) are a class of stimuli‐responsive materials, which have the ability of changing their shapes from a temporary state to their original or permanent shapes upon the application of external stimulus, such as light, solvent, heat, pH, electric field, or magnetic field . The numerous potential applications in information carriers, biomedical field, actuators, assembly/disassembly, and aerospace, have stimulated intense interest in this area over the last decade.…”
Section: Introductionmentioning
confidence: 99%